2005
DOI: 10.1089/scd.2005.14.587
|View full text |Cite
|
Sign up to set email alerts
|

Alteration on the Expression of IL-1, PDGF, TGF-β, EGF, and FGF Receptors and c-Fos and c-Myc Proteins in Bone Marrow Mesenchymal Stroma Cells from Advanced Untreated Lung and Breast Cancer Patients

Abstract: Previously, we reported a deficient cloning capacity of the bone marrow (BM) mesenchymal stem cells to give colony-forming unit fibroblast (CFU-F) and an inefficient confluence capacity of BM stromal cells in advanced untreated lung cancer patients (LCP) and breast cancer patients (BCP). Moreover, a decreased level of bFGF at day 7 in the conditioned media from BM CFU-F cultures was found in both cancer groups when compared to the normal range. The current study was specially undertaken, to evaluate the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Nonetheless, studies with mesenchymal cells that bear the cognate receptors (46) have reported conflicting results concerning motogenic properties, some of which can be accounted for by the use of different species, as mentioned above, but also possibly due to a lack in standards in the procedures to assay cell migration (47,48). The in vitro transmembrane chemotaxis assay (TCA), also named the modified Boyden chamber assay, is the assay of choice for identifying pro-or anti-motogenic compounds (49).…”
Section: Introduction Mmentioning
confidence: 99%
“…Nonetheless, studies with mesenchymal cells that bear the cognate receptors (46) have reported conflicting results concerning motogenic properties, some of which can be accounted for by the use of different species, as mentioned above, but also possibly due to a lack in standards in the procedures to assay cell migration (47,48). The in vitro transmembrane chemotaxis assay (TCA), also named the modified Boyden chamber assay, is the assay of choice for identifying pro-or anti-motogenic compounds (49).…”
Section: Introduction Mmentioning
confidence: 99%
“…In dataset2, mapping those uniquely selected genes by our method to cancer pathways left 12 genes, BID (GeneID: 637), CCNE2 (GeneID: 9134) [36], DVL3 (GeneID: 1857), FGF7 (GeneID: 2252), FGFR1 (GeneID: 2260), FGFR2 (GeneID: 2263), FZD4 (GeneID: 8322), MAP2K2 (GeneID: 5605), PDGFB (GeneID: 5155), PGF (GeneID: 5228) [37], PML (GeneID: 5371), and WNT1 (GeneID: 7471) ( Table S2 in File S5 ). Interestingly, we found that those genes, WNT1, FZD4, and DVL3 are enriched in the Wnt signaling pathway ( Figure S17 ) [38][41].…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports have shown that hBMSCs express receptors for PDGF and EGF and that proliferation can be stimulated by heparin-binding EGF-like growth factor (HB-EGF), which interacts with erbB4 and EGFR [Hofer et al, 2005;Krampera et al, 2005;Kratchmarova et al, 2005]. The receptors for EGF and PDGF are prototypical tyrosine kinase receptors present on most adherent cells, including MSCs [Ingram and Bonner, 2006], and are expressed on human MSCs as demonstrated by reported cellular responses [Hofer et al, 2005;Krampera et al, 2005]. Upon binding of EGF and PDGF, EGFR and PDGFR activate ERK (extracellular signal-regulated protein kinase), AKT (protein kinase B/akt) and PLC-␥ (phospholipase C-␥ ) which promote cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are also in line with those of Tamama et al [2006] who reported that EGFR ligands did not interfere with pluripotency of BMSCs or drive these cells into specific lineages. EGF and PDGF have been shown to inhibit collagen synthesis and alkaline phosphatase activity, and EGFR signaling was proposed as a negative regulator of osteogenic differentiation on BMSCs and preosteoblastic MC3T3 E1 cells [Chien et al, 2000;Gruber et al, 2004;Hofer et al, 2005]. The lack of significance in expression of Cbf-␣ 1 may be explained by the fact that the type I transcript of this transcription factor is also constitutively expressed in non-osseous mesenchymal tissues and plays a regulatory role in early stages of mesenchymal cell development [Banerjee et al, 2001].…”
Section: Discussionmentioning
confidence: 99%